2020
DOI: 10.1186/s12881-020-0956-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of association between common variants of uncoupling proteins genes and diabetic retinopathy in a Chinese population

Abstract: Background: The aim of this study was to explore the association between diabetic retinopathy (DR) and the variants of uncoupling proteins (UCPs) genes in a Chinese population of type 2 diabetes, in total and in patients of different glycemic status separately. Methods: This case-control study included a total of 3107 participants from two datasets, among which 662 were DR patients (21.31%). Eighteen tag single nucleotide polymorphisms (SNPs) of UCP1, UCP2, and UCP3 were selected as genetic markers. TaqMan pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The A-112C polymorphism was not associated with T2D in the study, but acted as part of the haplotype [−3826A/−112C/229Met] to increase the risk of T2D in Indians (Vimaleswaran et al 2009). In a Chinese population, the -112C allelic variant was identified as a risk factor for diabetic retinopathy (OR = 1.368 P = 0.004) (Jin et al 2020).…”
Section: A-1766g Polymorphism Of the Ucp1 Genementioning
confidence: 99%
“…The A-112C polymorphism was not associated with T2D in the study, but acted as part of the haplotype [−3826A/−112C/229Met] to increase the risk of T2D in Indians (Vimaleswaran et al 2009). In a Chinese population, the -112C allelic variant was identified as a risk factor for diabetic retinopathy (OR = 1.368 P = 0.004) (Jin et al 2020).…”
Section: A-1766g Polymorphism Of the Ucp1 Genementioning
confidence: 99%
“…After screening on the abstracts and full-text reports, 11 studies met with the inclusion criteria (Brondani et al 2012; Jin et al 2017; Jin et al 2020; Montesanto et al 2018; Rudofsky et al 2007; Shen et al 2014; Zhang et al 2014; Zhou et al 2018; Zietz et al 2006) [ 20 , 26 , 27 , 32 37 ]. Jin et al 2020 is comprised of 2 datasets, of which dataset 1 has been reported in Jin et al 2017 [ 34 , 35 ]. For Jin et al 2020 and Montesanto et al 2018, only the allelic data was able to be extracted [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jin et al 2020 is comprised of 2 datasets, of which dataset 1 has been reported in Jin et al 2017 [ 34 , 35 ]. For Jin et al 2020 and Montesanto et al 2018, only the allelic data was able to be extracted [ 35 , 36 ]. Therefore, dataset 2 of Jin et al 2020 as the data for Jin 2020 and Montesanto et al 2018 were used to calculate the pooled effect in the allelic model.…”
Section: Resultsmentioning
confidence: 99%
“…After screening on the abstracts and full-text reports, 11 studies met with the inclusion criteria [17,24,25,[30][31][32][33][34][35]. Jin et al 2020 is comprised of 2 datasets, of which dataset 1 has been reported in Jin et al 2017 [32,33]. For Jin et al 2020 and Montesanto et al 2018, only the allelic data was able to be extracted [33,34].…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Jin et al 2020 is comprised of 2 datasets, of which dataset 1 has been reported in Jin et al 2017 [32,33]. For Jin et al 2020 and Montesanto et al 2018, only the allelic data was able to be extracted [33,34]. Therefore, dataset 2 of Jin et al 2020 as the data for Jin 2020 and Montesanto et al 2018 were used to calculate the pooled effect in the allelic model.…”
Section: Studies Characteristicsmentioning
confidence: 99%